2012
DOI: 10.1007/s11033-012-2071-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid attenuates the expression of adhesion molecules by increasing endothelial nitric-oxide synthase activity

Abstract: We tried to study the possible effects of lipoic acid (LA) on adhesion molecule expression and its underlying mechanism in the prevention and treatment of cardiovascular disorders. Intercellular adhesion molecule-1 (ICAM-1) expression and endothelial nitric oxide synthase (eNOS) activity were determined after endothelial cells were exposed to high glucose in the absence and presence of LA. Coincubation of endothelial cells with high glucose for 24 h resulted in a significant increase of monocyte-endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Consistently, LA increases NO release by HUVECs (Figure 2) and nitrite/nitrate production in living animals (Figure 4). Our results are consistent with several studies showing that LA increases eNOS activity [1315], suggesting that this action of LA may be pharmacologically important. In addition to phosphorylation/de-phosphorylation, other post-translational modifications such as protein-protein interaction and the bioavailability of coenzyme tetrahydrobiopterin (BH4) also play a role in regulation of eNOS activity [12, 16, 17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistently, LA increases NO release by HUVECs (Figure 2) and nitrite/nitrate production in living animals (Figure 4). Our results are consistent with several studies showing that LA increases eNOS activity [1315], suggesting that this action of LA may be pharmacologically important. In addition to phosphorylation/de-phosphorylation, other post-translational modifications such as protein-protein interaction and the bioavailability of coenzyme tetrahydrobiopterin (BH4) also play a role in regulation of eNOS activity [12, 16, 17].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to our results, several other studies have shown that LA increases eNOS activity in both cultured cells and living animals [1315, 22, 29, 30], suggesting that LA may exert its therapeutic effects on those cardiovascular diseases through targeting eNOS. Although in the majority of those studies it is postulated that eNOS activation by LA is subsequent to its antioxidant action, direct evidence of this is lacking.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, the synergistic NO increase due to concurrent administration of α-lipoic acid and CSA is in line with reports showing that CSA (López-Ongil et al, 1998) and α-lipoic acid (Jin et al, 2013) increase nitric oxide synthase (NOS) activity. Further, NO production increases in inflamed colon due to non-enzymatic reaction of hydrogen peroxide (H 2 O 2 ) with arginine (Zhang et al, 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Low NO bioavailability has been shown to promote platelet activation [35], [36], [37] and to increase cellular adhesion [38], [39], [40]. Inhibition of endothelial nitric oxide synthase (eNOS) with L-NG-monomethyl Arginine citrate (L-NAME) increased leukocyte rolling and adhesion [41].…”
Section: Introductionmentioning
confidence: 99%